1993
DOI: 10.1113/jphysiol.1993.sp019696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of route of breathing on the ventilatory and arousal responses to hypercapnia in awake and sleeping dogs.

Abstract: SUMMARY1. The influence of the upper airway on the ventilatory and arousal responses to hypercapnia in wakefulness and sleep was investigated using a chronic animal model.2. Experiments were performed in five unrestrained dogs trained to sleep naturally in the laboratory. The animal rebreathed through a chronic tracheostoma (thus excluding the upper airway from the breathing circuit), or through the snout (intact upper airway). Resistance to breathing and volume of dead space during quiet tracheal breathing we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 44 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…The only advance our findings have made in understanding the nature of this REM-induced blunted response of ventilatory output and pressure development to the asphyxia of airway occlusion is to show that it occurs at the level of the neural activation of the diaphragm. Other respiratory mechanoreceptor reflex responses from lung stretch and from airway stimulation have also been shown to be blunted in phasic REM sleep (10,15,17,27,30). However, we think it unlikely that these reflexes are involved in the reduced ventilatory responses in REM sleep, because 1) they tend to be inhibitory, and blunting an inhibitory reflex should, if anything, enhance ventilation, and 2) the increase of ventilatory efforts over the duration of occlusion strongly suggests to us a buildup of chemical stimuli (5).…”
Section: Discussionmentioning
confidence: 99%
“…The only advance our findings have made in understanding the nature of this REM-induced blunted response of ventilatory output and pressure development to the asphyxia of airway occlusion is to show that it occurs at the level of the neural activation of the diaphragm. Other respiratory mechanoreceptor reflex responses from lung stretch and from airway stimulation have also been shown to be blunted in phasic REM sleep (10,15,17,27,30). However, we think it unlikely that these reflexes are involved in the reduced ventilatory responses in REM sleep, because 1) they tend to be inhibitory, and blunting an inhibitory reflex should, if anything, enhance ventilation, and 2) the increase of ventilatory efforts over the duration of occlusion strongly suggests to us a buildup of chemical stimuli (5).…”
Section: Discussionmentioning
confidence: 99%
“…This study adds to previous animal studies showing that arousability is less in active sleep compared with quiet sleep. Other animal studies have found delayed arousal in active sleep in response to hypercapnia (dogs, Phillipson et al 1977; Issa & Bitner, 1993; lambs, Fewell & Baker, 1989). Also arousal responses are slower in REM in response to hypoxia (Phillipson et al 1978; Henderson‐Smart & Read, 1979; Jeffery & Read, 1980; Neubauer et al 1981; Fewell & Baker, 1987) and airway stimulation or obstruction (Sullivan et al 1978; Davidson & Fewell, 1994).…”
Section: Discussionmentioning
confidence: 91%
“…In health, chemosensory responses to both hypercapnia [48] and hypoxia [49] are reduced in NREM and REM sleep [50]. Typically, responses to hypercapnia have been measured through Read's rebreathing protocol, in which P aCO 2 is increased by taking an individual's expired air and having them re-inspire it [48,[51][52][53]. Hypercapnic sensitivity can also be assessed through artificial increases in CO 2 through a breathing circuit [54].…”
Section: Ventilatory Neural Drive and Mechanical Output In Healthy In...mentioning
confidence: 99%